O 'Espelho dos Santos': analogias da Virgem Maria nos sermões de São Vicente Ferrer (1350-1419). - CAMBRAIA FRANCO, GUSTAVO (Scripta, 2017)
This article aims to present a study on the biblical and doctrinal exegesis that late medieval Valencian Dominican friar Saint Vincent Ferrer does on the subject of mariology. Based on the flow of the multisecular theological and literary patristic-scholastic tradition, on the strand of analogical thought and on a specular and symbolic worldview, the preacher presents in his sermons an extensive series of analogies, metaphors, allegories and biblical typologies by which he exalts the figure of the Virgin Mary and defines its meaning as icon and universal hagiographic model of the Middle Ages.